2005
DOI: 10.1007/s11912-005-0022-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of aging on the early detection, diagnosis, and treatment of breast cancer

Abstract: Patterns of care for women with breast cancer vary substantially with patient age. Older patients with breast cancer frequently receive less than standard management, resulting in poorer outcome. At diagnosis, the health status of older women with breast cancer affects survival and treatment decisions. Age-related comorbidity may limit diagnostic tests, narrow treatment options, and significantly increase mortality not related to breast cancer. Yet, for healthy older women with early-stage breast cancer, stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 68 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…Our results indicated that there were age differences in the use of GOs. Age-based differences in cancer care have been previously documented especially for diagnosis and treatment of breast cancer (Silliman et al 1989;Newschaffer et al 1996;Kearney et al 2000;Siebel and Muss 2005). Moreover, a sample of oncology professionals (medical, nursing, and radiography staff) surveyed to assess their attitudes toward older patients had persistently negative attitudes toward these patients regardless of profession, gender, and work experience (Kearney et al 2000).…”
Section: Disparities In Use Of Gynecologic Oncologistsmentioning
confidence: 98%
“…Our results indicated that there were age differences in the use of GOs. Age-based differences in cancer care have been previously documented especially for diagnosis and treatment of breast cancer (Silliman et al 1989;Newschaffer et al 1996;Kearney et al 2000;Siebel and Muss 2005). Moreover, a sample of oncology professionals (medical, nursing, and radiography staff) surveyed to assess their attitudes toward older patients had persistently negative attitudes toward these patients regardless of profession, gender, and work experience (Kearney et al 2000).…”
Section: Disparities In Use Of Gynecologic Oncologistsmentioning
confidence: 98%
“…Ecological studies, while allowing for analyses of cancer incidence and mortality trends in relation to FQHC availability, do not allow to control for individual-level factors, such as obesity, behavioral factors, socioeconomic characteristics, etc., which are necessary for estimating effect modification or controlling confounding. 43 Specifically, differential uptake of breast cancer treatment regimens by age and other demographic groups could affect the overall mortality or survival after diagnosis; 44 however, we could not take these individual factors into consideration. Although we attempted to adjust for county-level SES indicators, we could not fully account for differences by county.…”
Section: Fig 1 Federally Qualifiedmentioning
confidence: 99%
“…The changes in breast cancer mortality trends in Serbia in the same age groups were -2.0% per year and +2.3% per year, respectively. These age differences may reflect greater breast cancer awareness, better targeting of effective treatments, and response to treatments of younger rather than older women (Eaker et al, 2006;Siebel & Muss, 2005;August, Rea, & Sondak, 1994).…”
Section: Discussionmentioning
confidence: 99%